Friend or foe? The effects of harmonious and obsessive passion on entrepreneurs' well-being, strain and social loneliness. Issue 2 (3rd January 2022) - Bayraktar, Secil; Jiménez, Alfredo
Abstract : Purpose: Passion is considered a critical aspect of entrepreneurship. According to the dualistic model of passion (DMP), entrepreneurs' passion for their work can be harmonious or obsessive, leading to different personal and work outcomes. Drawing on DMP and the self-determination theory, this paper investigates these two types of passion for work and their effects on entrepreneurs' subjective well-being (SWB), psychological strain and social loneliness. Design/methodology/approach: The authors conducted a self-administered online survey with 312 entrepreneurs in Turkey. The authors selected the sample using purposive sampling and referrals through snowballing via associations, university start-up organizations, entrepreneur lists and personal networks. The data are analyzed using multiple regression analysis. Findings: The results show that harmonious passion is negatively related to strain, while obsessive passion is positively related to both strain and social loneliness. Furthermore, both types of passion are associated with higher SWB. Finally, age moderates the relationship between obsessive passion and SWB. Practical implications: The findings draw attention to another dark side to entrepreneurship and a useful perspective to raise awareness that entrepreneurs may think positively of obsessive passion and ignore the negative consequences. Originality/value: This study contributes to the literature by showing that both positive and negative consequences of passion may co-exist based on the entrepreneurs' self-perceptions. It also contributes to the very scarce research in non-western, emerging contexts in entrepreneurial passion research and constitutes the first study conducted on this topic in Turkey.